Psychological Drivers of Consumer´S Preferences for Green Transportation: an Empirical Analysis of Bikes´ Rental System at the University of Granada - Rodríguez-Priego, Nuria; Porcu, Lucía (Mediterranean Journal of Social Sciences, 2012)
We conducted a survey (n = 436) regarding consumer´s choice of sustainable transportation, toward a A survey wasconducted at the University of Granada (Spain) from May through August 2011, related to a system of bikes´ rental that has beenrecently introduced in the university community and whose expectations include its extension to the rest of the city of Granada. Thequestionnaire included items concerning attitude related to the behavior, individual´s perceived control, subjective norms and personalmoral norms, variables used in the Theory of Reasoned Action from Fishbein and Ajzen (1975), the Theory of Planned Behavior (Ajzen& Madden, 1986) and the Norm-Activation Theory (Schwartz, 1977). The main objective of this study was to examine those factors thatcould affect the transport choice behavior of consumers toward more sustainable energy consumption patterns, meaning the decision touse (or not to use) the bikes´ rental system by the university community. The results corroborate the hypothesis tested, and positivecorrelations between the variables and the behavioral intention.